El-Qitar - McClellan, Thomas Lynn, 1939- (Turnhout, Belgium)
xxiii, 511 sayfa
Keywords: “Located along the River Euphrates, in modern-day Syria, el-Qitar was a mountain fortress of the Middle Bronze Age. Excavations, fully analysed in this volume for the first time, revealed extensive fortifications, with two city gates, multiple towers, a fosse, an earthen rampart, and casemate walls, in addition to a public building lined with orthostats of the Middle Bronze Age. After a short time, the site was abandoned and, following a gap of several centuries, re-settled in the Late Bronze Age. It was then that upper and lower settlements were established within the old fortifications, possibly in the wake of Hittite campaigns in Northern Syria that destroyed nearby towns. Detailed analyses of ceramics and objects explore the possibility that el-Qitar was re-occupied by local refugees. This volume traces the changing function of the site over time, arguing that el-Qitar might have been the site known as Dur Samsi-Addu during the Middle Bronze Age, and Til-Abnu of the Late Bronze Age. The latest construction episode belongs to the modern-day Tishreen Dam.” --